2000
DOI: 10.1029/1999gl010769
|View full text |Cite
|
Sign up to set email alerts
|

Detection of daytime sprites via a unique sprite ELF signature

Abstract: Abstract. On August 14, 1998, 3 separate daytime sprite events were detected via a unique extremely low frequency (ELF) sprite signature. The onset of the sprite ELF signatures was delayed by 11.0-13.2 ms from positive cloudto-ground strokes which had attained exceptionally large charge moment (charge times height) changes of 3900-6100 C-km. It is shown that a charge moment change of 6100 C.km may have been sufficient for conventional breakdown at _•54 km altitude, assuming an experimentally measured ion condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 19 publications
6
41
2
Order By: Relevance
“…This contradicts with observations since the measured lightning charge moment changes in TGF-associated strokes are 50-500 times smaller than what the runaway theory predicts (Cummer et al, 2005). However, it is still possible that some TGFs are generated by enormous lightning discharges with charge moment changes of several thousands of C km (Stanley et al, 2000;Cummer and Füllekrug, 2001).…”
Section: V Surkov and M Hayakawa: Underlying Mechanisms Of Transcontrasting
confidence: 50%
See 2 more Smart Citations
“…This contradicts with observations since the measured lightning charge moment changes in TGF-associated strokes are 50-500 times smaller than what the runaway theory predicts (Cummer et al, 2005). However, it is still possible that some TGFs are generated by enormous lightning discharges with charge moment changes of several thousands of C km (Stanley et al, 2000;Cummer and Füllekrug, 2001).…”
Section: V Surkov and M Hayakawa: Underlying Mechanisms Of Transcontrasting
confidence: 50%
“…Neubert et al, 2008;Pasco, 2010;Raizer et al, 2010). The polarity asymmetry of sprite-producing lightning (Boccippio et al, 1995;Lyons, 2006;Williams et al, 2007), as well as the fact that the charge moment change of the causative +CG must be greater than ∼500 C km to produce sprites (Stanley et al, 2000;, is far from being well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also it has been estimated that an unusually large charge moment change of about 8000 C-km is required to initiate a daytime sprite at a 50-km altitude (Fernsler and Rowland, 1996). Stanley et al (2000) detected 3 separate daytime sprites on 14 August, 1998, via a unique sprite ELF signature recorded at a site in New Mexico, following exceptionally large lightning discharges. Farges et al (2005) were the rst to measure infrasound waves emitted from sprites past sunrise and onwards into the daytime, and suggested the occurrence of daytime sprites.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 2a, the sferic signal for the positive sprite also contains a second slow pulse that could be unambiguously identified due to the lack of higher frequency (> 1 kHz) radiation (e.g., Stanley et al 2000;Füllekrug et al 2001;Hu et al 2002;Lu et al 2013), which is attributed to the current flow along sprite bodies (Cummer et al 1998;Pasko et al 1998). By examining sprite-associated sferics with distinct sprite current signal, we found that a discernible sprite current signal, not surprisingly, are unique to those sprites that appeared bright (with a relatively large vertical scale).…”
Section: Observations and Methodsmentioning
confidence: 99%